The Axiological Wager in the Linguistic and Literary Construction of the Dramatic Text (The International Journal of Educational Sciences and Arts, 2025)
This study addresses the "Axiological Wager" within the genre of theatre, specifically focusing on "Post-dramatic Theatre." It employs a methodology that integrates literary-critical analysis with linguistic-pragmatic analysis. The study aims to trace the markers of the "axiological impasse" in contemporary theatre, which manifests literarily through features such as "improvisation", "audience participation" in the performance, and the deconstruction of the classical spatial framework.To substantiate this thesis, the linguistic analysis delves into the deep structures of the dramatic text, revealing how this axiological collapse is constructed. Through analytical examples, the research demonstrates how post-dramatic theatre utilizes mechanisms of "Semantic Bleaching" for value-laden vocabulary, how it employs "Speech Acts" as a tool for "impact" rather than "message", and how it culminates in "Semiotic Contradiction," where the physical performance "deconstructs" what the verbal utterance asserts.The study concludes that the axiological wager is no longer contingent on the "content" of the text, but has transformed into a wager on the capacity of "language" itself to carry value, thereby transferring the burden of "meaning production" onto the audience.
Keywords: Axiological Wager; Post-dramatic Theatre; Linguistic Construction; Theatrical Pragmatics; Semiotics of Performance; Axiological Impasse